COMPREHENSIVE EVALUATION SYSTEM ON BAHASA INDONESIA LEARNING OUTCOME (Universitas Negeri Semarang, 2015)
This study aims to develop a comprehensive evaluation system on Bahasa Indonesia learning outcome for Junior High School students based on Gall & Borg model. The study has some findings. First, the SWOT analysis results show the need of developing a comprehensive evaluation system on Indonesian learning outcomes at grade level. Second, the rules of the comprehensive evaluation system are packed into three parts; the conceptual rules of learning outcomes evaluation, the implementation rules of the evaluation of learning outcomes at the beginning, on the process, and at the end of the study, and follow-up of the learning outcomes evaluation. Third, the research product in the form of a comprehensive evaluation system of learning outcomesmanual book for Indonesian teachers is considered feasible by expert and very well perceived by the teacher. Fourth, the try-out results with the technique of one-sample t-test (one-tail) at a 95% confidence level showed a significant increase on teachers’ pedagogical competence. This is shown by the group A, t-value 6.6149 is greater than the table of t-values1746, group B, t-value 7.8257 is greater than the table of t-values 1729, and the group C 10.0857 t-count is greater than the table of t-values1697. Thus, this comprehensive Indonesian learning outcomes evaluation system is effective to improve teachers' pedagogical competence.